1986
DOI: 10.1111/j.1749-6632.1986.tb48061.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Aspects of Neurofibromatosisa

Abstract: Although the genetic pattern in NF has been definitely established as autosomal dominant, more precise data regarding penetrance, natural history, prevalence, and heterogeneity are needed for the counseling of families. NF is the prototypic disorder for the study of the biologic mechanisms of variable expressivity. The widely cited prevalence figure of Crowe is probably too high; thus the mutation ratio estimation in NF is among the highest in man but close to other common Mendelian disorders. With the existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 11 publications
0
38
0
2
Order By: Relevance
“…Neurofibromatosis type 1 (NF1) (OMIM 162200) is an autosomal dominant disorder with café-au-lait spots, neurofibromas, Lisch nodules, axillary and inguinal freckling, optic nerve glioma, and skeletal abnormalities [Carey et al, 1986]. The responsible gene, NF1, encodes a GTPase activating protein (neurofibromin) that acts as a negative regulator of RAS signaling [Xu et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibromatosis type 1 (NF1) (OMIM 162200) is an autosomal dominant disorder with café-au-lait spots, neurofibromas, Lisch nodules, axillary and inguinal freckling, optic nerve glioma, and skeletal abnormalities [Carey et al, 1986]. The responsible gene, NF1, encodes a GTPase activating protein (neurofibromin) that acts as a negative regulator of RAS signaling [Xu et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibromatosis type 1 (NF1; MIM# 162200) is an autosomal disorder with an estimated incidence of 1 in 3500 live births (Carey et al, 1986). NF1 is due to autosomal dominant loss-of-function mutations of the NF1 gene (neurofibromin 1; NM_000267), a tumour suppressor gene located at 17q11.2 and containing 60 translated exons distributed over ~300 kb.…”
Section: Introductionmentioning
confidence: 99%
“…The RASopathy neurofibromatosis 1 (NF1) is an autosomal dominant hereditary cancer syndrome that affects~1 in 3000 individuals [1]. The diagnosis of NF1 is based on National Institutes of Health clinical consensus criteria [2,3], with the main clinical features including multiple café-au-lait macules, axillary freckling, Lisch nodules, optic pathway gliomas, peripheral nerve sheath tumors, multiple forms of cognitive dysfunction, and a higher risk of cancers such as pheochromocytoma and breast cancer in young women.…”
Section: Introduction To Neurofibromatosismentioning
confidence: 99%
“…NF1 is a highly variable disease and considerable differences in clinical symptoms are noted within the same family [1]. Notably, phenotype-genotype correlation studies have suggested that the type of mutation in the NF1 gene does not solely account for the observed phenotype, with the exception of patients carrying chromosomal deletions (microdeletions) [6].…”
Section: Introduction To Neurofibromatosismentioning
confidence: 99%